Prediction Of Purento-Inflammatory Complications In Open Fractures Of Long Tubular Bones - J. T. Tukhtaev (Genius Journals, 2024)
The course of many inflammatory and purulent diseases, including those with open fractures of long tubular bones, has changed significantly and acquired a hidden nature, which poses significant difficulties both in diagnosis and in treatment. Numerous factors that determine the characteristics of the outcome in open fractures complicated by the development of wound infection include the state of the immune and antioxidant status of the macroorganism. The most important of them are: studying the state of the immune system, “LPO antioxidants” at different stages of the development of surgical infection, determining the role of changes in peroxide status in the formation of the immune response, as well as the development of criteria for early prediction of infectious complications
Keywords: purulent-inflammatory complications; prognosis; open fractures